2014
DOI: 10.1177/0017896913516096
|View full text |Cite
|
Sign up to set email alerts
|

Defining older adults’ perceived causes of hypertension in the Brief Illness Perception Questionnaire

Abstract: Objectives: This study sought to make the Brief Illness Perception Questionnaire (BIPQ) to be more informative about illness representation among older adults with hypertension. The authors developed categories for coding the open-ended question regarding cause of illness in the BIPQ – a pervasive quantitative measure for illness representation. Methods: Using inductive thematic analysis, the authors described categories which emerged from analysing the open-ended question of the BIPQ applied to patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…This finding suggests that the STOFHLA measure taps other processes that influence recall of health information. For example, the previous literature suggests that patients' beliefs about their illness, or their illness representation, influence their self-care behavior (e.g., Duwe et al, 2014;Leventhal et al, 1983). Although patients' illness representations are partly associated with health knowledge, presumably through experience with the illness (e.g., Chin et al, 2009), our measure of hypertension knowledge may not have adequately measured this construct.…”
Section: Discussionmentioning
confidence: 94%
“…This finding suggests that the STOFHLA measure taps other processes that influence recall of health information. For example, the previous literature suggests that patients' beliefs about their illness, or their illness representation, influence their self-care behavior (e.g., Duwe et al, 2014;Leventhal et al, 1983). Although patients' illness representations are partly associated with health knowledge, presumably through experience with the illness (e.g., Chin et al, 2009), our measure of hypertension knowledge may not have adequately measured this construct.…”
Section: Discussionmentioning
confidence: 94%
“…The BIPQ also contained an open-ended question: ‘Please list the three most important factors that you think caused your high blood pressure’. Elsewhere, Duwe et al (2014) have identified different categories of causal beliefs from responses to this question: behavioural, natural, physical, psychosocial and supernatural.…”
Section: Methodsmentioning
confidence: 99%
“…The perceived cause of illness is an important but understudied IR dimension (Duwe et al, 2014). Understanding older adults’ causal beliefs is, therefore, important for patient–provider communication, individual coping and adherence to self-care (Perkins-Porras et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations